A coating and its preparation method, product and application

The formation of coating on the matrix material by chemical vapor deposition method solves the problem of coating crust phenomenon, achieves efficient anti-oxidation and ablation properties, and extends the service life of the matrix material.

CN116219399BActive Publication Date: 2025-04-08JIANGYOU TIANLI XINTAO CARBON MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310017784.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-04-08
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The prior art is prone to crust when forming the coating on the surface of the substrate material, resulting in insufficient bonding between the coating and the substrate material and inability to effectively protect the substrate material, especially in high temperature environments.

Method used

The coating is formed on the matrix material by chemical vapor deposition. The specific process conditions are: heating temperature 1095-1105℃, pressure 1500-2500Pa, the composite gas is a carbon source precursor and nitrogen, and the residence time is 7s-12s.

Benefits of technology

The formed coating has high oxidation resistance and ablation resistance, can effectively protect the matrix material, extend its service life, and there is no crust problem in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004041197580000081
    Figure BDA0004041197580000081
Patent Text Reader

Abstract

The present application relates to the technical field of coating preparation, and specifically discloses a coating and its preparation method, products, and applications. The coating is prepared by chemical vapor deposition, and the conditions of chemical vapor deposition are: heating temperature is 1095-1105°C, pressure is 1500-2500Pa, composite gas is carbon source precursor and nitrogen, and the residence time of the composite gas is 7s-12s. The loss of the coating at 2000°C for 100h △W%≤3.81%, and the mass ablation rate Rm≤5.0mg / s at 3000°C for 20s, which can improve the oxidation resistance and ablation resistance of the substrate, and does not produce crusting and carbon black problems. The coating prepared in this application is mainly used in photovoltaic thermal field components and heat shielding components to improve the oxidation resistance and ablation resistance of photovoltaic thermal field components and heat shielding components, thereby extending the service life of photovoltaic thermal field components and heat shielding components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating preparation, and more specifically to a coating and a preparation method thereof, a product, and an application thereof. Background Art

[0002] Photovoltaic thermal field components include crucibles, flow guide tubes, and insulation tubes. They are mainly used in the manufacture of monocrystalline silicon, polycrystalline silicon, etc. Photovoltaic thermal field components are consumables in the silicon product preparation process, and the performance of photovoltaic thermal field components directly affects the quality of silicon products. Photovoltaic thermal field components are mainly used in high-temperature environments above 1600°C. Therefore, the current research on photovoltaic thermal field components focuses on high-temperature tolerance, high-temperature oxidation resistance, etc., to extend the service life of photovoltaic thermal field components.

[0003] Heat shield components mainly include engines, turbines, nose cones, thermal insulation linings, fairings and trims, and are important components of aircraft. Heat shield components in aircraft are mainly used at temperatures of 1000-2000°C, so heat shield components need to withstand higher temperatures and withstand high-temperature oxidation to extend the service life of heat shield components.

[0004] At present, in the relevant technology, there are two main means to improve the high temperature and high temperature oxidation resistance of photovoltaic thermal field components and heat shielding components, specifically: modifying the base material and forming a coating on the surface of the base material. However, the current modification technology can only make the modified material suitable for environments below 1000°C, so forming a coating on the surface of the base material has become the focus of research.

[0005] The methods for forming a coating on a substrate mainly include embedding method, slurry method, hydrothermal electrophoretic deposition method and chemical vapor deposition method. The embedding method, slurry method and hydrothermal electrophoretic deposition method have the problems of high cost and poor bonding between the coating and the substrate material. Therefore, the coating obtained cannot effectively protect the substrate material. The chemical vapor deposition method has a simple process and a high bonding force between the coating and the substrate material. However, when the coating is prepared by chemical vapor deposition method, the coating is prone to crusting, carbon black and other problems. Summary of the invention

[0006] In order to form a coating on the surface of a substrate material and avoid the coating crusting phenomenon, the present application provides a method for preparing a coating, and the coating, product and application obtained thereby.

[0007] In the first aspect, the present application provides a method for preparing a coating, characterized in that it includes the following steps: forming a coating on a substrate by chemical vapor deposition, the conditions of the chemical vapor deposition are: the heating temperature is 1095-1105°C, the pressure is 1500-2500Pa, the composite gas is a carbon source precursor and nitrogen, and the residence time of the composite gas is 7s-12s.

[0008] In the present application, a coating is formed on a substrate by chemical vapor deposition, and the obtained coating has high oxidation resistance and ablation resistance, can effectively protect the substrate, and prolong the service life of the substrate.

[0009] The substrate is placed in a chemical deposition furnace, a composite gas consisting of a carbon source precursor and nitrogen is introduced, and then heated and the pressure is adjusted. At a heating temperature of 1095-1105°C, the carbon source precursor is cracked to form deposited carbon. The deposited carbon is deposited on the surface of the substrate to form a coating, thereby protecting the substrate.

[0010] The conditions for chemical vapor deposition are: heating temperature of 1095-1105°C, pressure of 1500-2500Pa, residence time of composite gas of 7s-12s, and flow rate of composite gas of 35m 3 / h-50m 3 / h.

[0011] Under the above process conditions, a coating is formed on the substrate, which can improve the surface state of the substrate, and no crusting problem occurs during the preparation of the coating. The process of crusting of the coating is generally as follows: During the deposition process, due to poor control of the deposition conditions, carbon will accumulate on the surface of the substrate to form aggregated solids, which are in the form of shells or spots. At the same time, the coating can improve the antioxidant and ablation resistance of the substrate. At a test temperature of 2000°C, the weight loss percentage of the coating after 100h is less than or equal to 3.81%; at a test temperature of 3000°C, after 20s of ablation, the mass ablation rate of the coating is less than or equal to 5.0mg / s.

[0012] When the heating temperature is lower than 1095°C, the high-temperature weight loss percentage of the coating is 5.64%, and the mass ablation rate is 5.6 mg / s, so the coating's antioxidant and ablation resistance are low, and a crusting problem occurs, which makes it impossible to effectively protect the substrate.

[0013] When the heating temperature is higher than 1105°C, the coating formed on the substrate will produce a crusting problem. In the process of preparing single crystal silicon, the substrate at the crusting location is exposed to the air and often becomes a site of air attack, making the coating unable to effectively protect the substrate and reducing the service life of the substrate.

[0014] When the heating temperature is 1095-1105°C, the pressure is adjusted to 1500-2500Pa, the residence time of the composite gas is 7s-12s, and a coating is formed on the surface of the substrate without causing crusting problems.

[0015] In the present application, when the pressure is less than 1500Pa, the anti-oxidation and anti-ablation properties of the coating are low. At a test temperature of 2000°C, the weight loss percentage of the coating after 100h is greater than 5%; at a test temperature of 3000°C, after 20s of ablation, the mass ablation rate of the coating is greater than 5.0mg / s. Therefore, photovoltaic thermal field components and heat shielding components cannot meet the use requirements at a temperature of 1000-2000°C. When the pressure is greater than 2500Pa, the coating formed on the surface of the substrate has the problem of shell warping, and the coating cannot effectively protect the substrate, thereby shortening the service life of the substrate.

[0016] When the residence time of the composite gas is less than 7s, the high-temperature weight loss percentage of the coating is greater than 5%, the mass ablation rate is greater than 5.0mg / s, the coating's antioxidant and ablation resistance are low, and cannot meet the use requirements of photovoltaic thermal field components and heat shielding components; when the residence time of the composite gas is greater than 12s, the coating on the substrate surface will produce a crusting problem, which also reduces the coating's antioxidant and ablation resistance, thereby shortening the substrate's service life.

[0017] Preferably, the heating temperature is 1100-1105° C., the pressure is 1500-2000 Pa, and the residence time of the composite gas is 7s-10s.

[0018] Preferably, the heating temperature is 1100-1105° C., the pressure is 1800-2000 Pa, and the residence time of the composite gas is 7s-8s.

[0019] More preferably, the heating temperature is 1100° C., the pressure is 2000 Pa, and the residence time of the composite gas is 8 s.

[0020] In one embodiment, the heating temperature may be 1095°C, 1098°C, 1100°C, 1102°C, or 1095°C.

[0021] In one embodiment, the pressure may be 1500Pa, 1600Pa, 1700Pa, 1800Pa, 1900Pa, 2000Pa, 2200Pa or 2500Pa.

[0022] In one embodiment, the residence time of the composite gas may be 7s, 8s, 9s, 10s, 11s or 12s.

[0023] In one embodiment, the volume ratio of the carbon source precursor to the nitrogen gas is 1:(1-3).

[0024] In the present application, the composite gas is a mixture of a carbon source precursor and nitrogen, and the volume ratio of the carbon source precursor to the nitrogen is 1:(1-3). The carbon source precursor is cracked at 1095-1105°C to generate deposited carbon, which is gradually deposited on the surface of the substrate to form a coating, effectively protecting the substrate.

[0025] The role of nitrogen is to dilute the carbon source precursor to a certain extent, reducing the possibility of crusting. Therefore, the volume of nitrogen is equal to or greater than the volume of the carbon source precursor. When the volume of nitrogen is less than the volume of the carbon source precursor, the probability of crusting of the coating on the substrate increases. When the volume of nitrogen is more than 3 times the volume of the carbon source precursor, it may cause the coating formed on the substrate to be incomplete, directly losing the protective significance of the coating to the collective.

[0026] Preferably, the volume ratio of the carbon source precursor to the nitrogen is 1:(1-2).

[0027] Further preferably, the volume ratio of the carbon source precursor to the nitrogen gas is 1:2.

[0028] In one embodiment, the carbon source precursor is selected from alkanes, alkenes, and alkynes having 1 to 4 carbon atoms.

[0029] More preferably, the carbon source precursor is methane.

[0030] In one embodiment, the substrate is a carbon / carbon composite material.

[0031] Preferably, the density of the carbon / carbon composite material is (1.2-1.5)±0.01 g / cm 3 .

[0032] In the present application, the matrix is ​​a carbon / carbon composite material. The carbon / carbon composite material can be a commercially available product, which can be purchased from Zhejiang Wanju New Materials Technology Co., Ltd.; the carbon / carbon composite material can also be self-made; the preparation process of the carbon / carbon composite material includes the following steps: using carbon fiber as a raw material (the carbon fiber is from Zhongfu Shenying Company, the product model is SYT49S-12K, or Toray Company of Japan, the product model is T700SC-12K), the carbon fiber is prepared into a carbon fiber mesh and a carbon fiber woven fabric respectively; then the carbon fiber mesh is prepared into a carbon fiber mesh tire, and the carbon fiber woven fabric is prepared into a carbon fiber cloth; finally, the carbon fiber mesh tire and the carbon fiber cloth are compounded by needle-punched composite technology to obtain a carbon fiber preform, and the density of the carbon fiber preform is (0.4-0.5) ± 0.03g / cm 3The carbon fiber preform is densified by chemical vapor deposition, that is, the density of the carbon fiber preform is increased to obtain a carbon / carbon composite material. The density of the carbon / carbon composite material is (1.2-1.5) ± 0.01 g / cm 3 .

[0033] In a second aspect, the present application provides a coating prepared using the coating preparation method described in the present application.

[0034] The coating is formed on a substrate of a carbon / carbon composite material using the coating preparation method described in the present application. The coating has high oxidation resistance and ablation resistance, with a loss of △W%≤3.81% for 100 hours at 2000°C, and a mass ablation rate Rm≤5.0mg / s for 20 seconds at 3000°C. In addition, no crusting problem is generated during the preparation process of the coating, and the substrate can be effectively protected.

[0035] In a third aspect, the present application provides a product, which includes the coating prepared in the present application.

[0036] Preferably, the matrix is ​​a carbon / carbon composite material.

[0037] Further preferably, the density of the carbon / carbon composite material is (1.2-1.5)±0.01 g / cm 3 .

[0038] In one embodiment, the article is a photovoltaic thermal field component or a heat shielding component. The photovoltaic thermal field component is a crucible, a guide tube or a heat insulation tube; the heat shielding component is an engine, a turbine, a nose cone, a heat insulation lining, a fairing or a regulating sheet.

[0039] In a fourth aspect, the present application provides an application of a coating in photovoltaic thermal field components and heat shielding components.

[0040] Photovoltaic thermal field components are mainly used to produce silicon products. Photovoltaic thermal field components mainly include crucibles, flow guide tubes, insulation tubes, etc. Crucibles are mainly used to support the quartz crucibles in the inner layer of the single crystal furnace; flow guide tubes are used to prevent external heat from being conducted to the inside of the single crystal furnace to ensure the growth rate of silicon rods; the insulation tube is used to prevent the heat inside the single crystal furnace from being conducted outwards and to construct a thermal field space.

[0041] It is understood that photovoltaic thermal field components are mainly used in high temperature environments above 1600°C. Photovoltaic thermal field components need to withstand higher temperatures and withstand high temperature oxidation. Applying the coating prepared in this application to photovoltaic thermal field components can improve the antioxidant and ablation resistance of photovoltaic thermal field components and extend the service life of photovoltaic thermal field components.

[0042] The heat shielding components mainly include engines, turbines, nose cones, thermal insulation linings, fairings and trims, and are important components of aircraft. The heat shielding components need to withstand high temperatures of 1000-2000°C and withstand high-temperature oxidation during service. Therefore, the coating prepared in this application is applied to the heat shielding components to improve the anti-oxidation and anti-ablation properties of the heat shielding components, and effectively protect the heat shielding components.

[0043] In summary, this application has the following beneficial effects:

[0044] 1. The present application forms a coating on a substrate, and there is no crusting problem during the preparation of the coating. The coating has high oxidation resistance and ablation resistance, effectively protecting the substrate, thereby extending the service life of the substrate or the product;

[0045] 2. In the preparation process of the coating of the present application, the heating temperature is preferably 1095-1105°C, the pressure is 1500-2500Pa, the residence time of the composite gas is 7s-12s, the loss of the coating after 100h at 2000°C is △W%≤3.81%, the mass ablation rate Rm≤5.0mg / s at 3000°C for 20s, and no crusting occurs;

[0046] 3. In the preparation method of the coating of the present application, the heating temperature is preferably 1100-1105°C, the pressure is 1800-2000Pa, the residence time of the composite gas is 7s-8s, the loss of the coating after 100h at 2000°C is △W%≤2.68%, and the mass ablation rate Rm≤3.7mg / s at 3000°C for 20s. DETAILED DESCRIPTION

[0047] The present application is further described in detail below with reference to the embodiments.

[0048] Example

[0049] Example 1

[0050] This application uses a carbon / carbon crucible purchased from Zhejiang Wanju New Materials Technology Co., Ltd. as a substrate to form a coating on the surface of the carbon / carbon crucible. The specific process conditions include:

[0051] The density of carbon / carbon crucible is 1.5±0.01g / cm 3 ;

[0052] The carbon / carbon crucible is placed in a 3m*3.5m vertical chemical deposition furnace, and the composite gas is introduced. The heating temperature is 1100℃, the pressure is 2000Pa, the residence time of the composite gas is 8s, and the flow rate of the composite gas is 45m 3 / h, to obtain a carbon / carbon crucible with a coating (hereinafter referred to as crucible);

[0053] The composite gas is methane (carbon source precursor) and nitrogen, and the volume ratio of the methane to the nitrogen is 1:2.

[0054] The differences between Example 2 to Example 9 and Example 1 are shown in Table 1.

[0055] Table 1 Parameters of Examples 2-9 and 1

[0056] Group Heating temperature / ℃ Pressure / Pa Residence time / s Example 1 1100 2000 8 Example 2 1095 2000 8 Example 3 1105 2000 8 Example 4 1100 1500 8 Example 5 1100 1800 8 Example 6 1100 2500 8 Example 7 1100 2000 7 Example 8 1100 2000 10 Example 9 1100 2000 12

[0057] Example 10

[0058] The difference between Example 10 and Example 1 is that the volume ratio of the methane (carbon source precursor) and the nitrogen in Example 10 is 1:1.

[0059] Embodiment 11

[0060] The difference between Example 11 and Example 1 is that the volume ratio of methane (carbon source precursor) to nitrogen in Example 11 is 1:3.

[0061] Example 12

[0062] The difference between Example 12 and Example 1 is that the density of the carbon / carbon crucible in Example 12 is 1.2±0.01 g / cm 3 .

[0063] Comparative Example

[0064] The differences between Comparative Examples 1-7 and Step S3 of Example 1 are shown in Table 2.

[0065] Table 2 Parameters of Comparative Examples 1-7 and Example 1

[0066] Group Heating temperature / ℃ Pressure / Pa Residence time / s Example 1 1100 2000 8 Comparative Example 1 1090 2000 8 Comparative Example 2 1110 2000 8 Comparative Example 3 1100 1400 8 Comparative Example 4 1100 2700 8 Comparative Example 5 1100 2000 4 Comparative Example 6 1100 2000 14 Comparative Example 7 1090 2700 14

[0067] Performance testing

[0068] Test 1: Performance test of coating

[0069] The crucibles were prepared using the preparation methods described in Examples 1-12 and Comparative Examples 1-7, and then subjected to oxidation resistance testing, ablation resistance testing, appearance observation, and bonding strength testing.

[0070] The weight loss method was used to test the oxidation resistance. The crucible was weighed and recorded as m0. The crucible was placed in a high-temperature furnace with a temperature of 2000°C. After 100 hours, the crucible was weighed and recorded as m1. The loss △W% was calculated using formula (2). △W% < 5% met the requirements. The specific test results are shown in Table 3.

[0071] According to GJB 323A-96, the crucible was subjected to ablation test using an oxyacetylene ablation device. The ablation conditions were as follows: acetylene pressure was 0.095 MPa, flow rate was 1.116 m 3 / h; oxygen pressure is 0.4MPa, flow rate is 1.512m 3 / h; the distance from the oxyacetylene gun mouth to the center of the ablation surface of the crucible is 10mm, the ablation temperature is 3000℃, and the ablation time is 20s. The mass ablation rate Rm is calculated using formula (3), and Rm≤5.0mg / s meets the requirements. The specific test results are shown in Table 3.

[0072] In formula (3), Rm represents the mass ablation rate; m0 represents the mass before ablation (g); m1 represents the mass after ablation (g); and t represents the ablation time (t).

[0073] The bonding strength between the coating and the substrate in the crucible was tested by the tensile method. The test standard was ASTM C633. The specific test results are shown in Table 3.

[0074] Table 3 Test results

[0075] Group △W% Rm(mg / s) Appearance Bonding strength / MPa Example 1 2.26% 2.9 No crust 166 Example 2 2.36% 3.1 No crust 148 Example 3 2.33% 3.3 No crust 155 Example 4 3.12% 3.9 No crust 151 Example 5 2.53% 3.5 No crust 158 Example 6 3.28% 4.1 No crust 172 Example 7 2.68% 3.7 No crust 166 Example 8 3.45% 4.4 No crust 165 Example 9 3.72% 4.8 No crust 166 Example 10 3.73% 4.6 No crust 173 Embodiment 11 3.81% 5.0 No crust 160 Example 12 2.30% 3.0 No crust 158 Comparative Example 1 5.64% 5.6 With crust, spotted distribution / Comparative Example 2 4.95% 4.9 With crust, shell-like distribution / Comparative Example 3 6.55% 6.1 With crust, spotted distribution / Comparative Example 4 6.22% 5.9 With crust, shell-like distribution / Comparative Example 5 7.86% 6.4 No crust 166 Comparative Example 6 7.43% 6.1 With crust, spotted distribution / Comparative Example 7 8.77% 6.9 With crust, shell-like distribution /

[0076] *The “ / ” in Table 3 indicates that during the preparation of the coating, crusting problems occurred and the shear strength test was not performed.

[0077] It can be seen from Examples 1-12 and Comparative Examples 1-7 and Table 3 that the coating is formed on the surface of a carbon / carbon crucible, that is, on the surface of a carbon / carbon composite material, by using the coating preparation method described in the present application, and the coating can effectively protect the carbon / carbon composite material. The coating has a loss of ΔW%≤3.81% at 2000°C for 100h, a mass ablation rate Rm≤5.0mg / s at 3000°C for 20s, and no crusting phenomenon occurs during the coating preparation process, and the shear strength is above 140MPa.

[0078] In particular, for the coating prepared in Example 1, the heating temperature was 1100° C., the pressure was 2000 Pa, the residence time was 8 s, the coating loss △W% was 2.26%, and the mass ablation rate Rm was 2.9 mg / s.

[0079] Combining Examples 1-3 and Comparative Examples 1-2 and Table 3, it can be seen that when other process conditions remain unchanged, during the preparation of the coating, the heating temperature of the chemical vapor deposition is 1095-1105°C, and as the heating temperature gradually increases, the loss △W% and mass ablation rate Rm of the coating show a trend of first decreasing and then increasing. This indicates that the protective ability of the coating on the carbon / carbon composite material gradually increases, and when the heating temperature exceeds 1100°C, the protective ability of the coating on the carbon / carbon composite material gradually decreases.

[0080] It can be seen from Examples 1-3 and Comparative Examples 1-2 and Table 3 that during the preparation of the coating, the heating temperature of the chemical vapor deposition is 1095-1105°C. When the heating temperature is lower than 1095°C or higher than 1105°C, a crusting problem occurs, and the substrate cannot be effectively protected.

[0081] Combining Examples 1, 4-6 and Comparative Examples 3-4 and Table 3, it can be seen that in the preparation process of the coating, other processes remain unchanged, and as the pressure gradually increases, the loss of the coating △W% and the mass ablation rate Rm also show a trend of first decreasing and then increasing. This shows that the protective ability of the coating on the carbon / carbon composite material gradually becomes stronger, and when the pressure is greater than 2000Pa, the protective ability of the coating on the carbon / carbon composite material gradually becomes worse.

[0082] It can be seen from Examples 1, 4-9 and Comparative Examples 5-6 and Table 3 that when the residence time of the mixed gas is 7s-12s, no crusting problem occurs during the preparation of the coating, and the coating loss △W% is less than 5%, and the mass ablation rate Rm≤5.0mg / s.

[0083] Test 2: Crucible service life test

[0084] The crucibles prepared in Examples 1-2, 6 and 9 of the present application were used to prepare single crystal silicon, and the service life of the crucibles was tested. During the service of the crucible, as time goes by, the coating is gradually consumed, and the air and silicon vapor react with the matrix in the crucible to destroy the carbon fiber, thereby reducing the tensile strength of the crucible. When the strength drops by more than 50%, the crucible fails directly.

[0085] The preparation of single crystal silicon adopts the Czochralski method, which includes: total feed amount of 750kg, total crystal length of 1850mm, crystal rotation speed of 8rpm / min, crucible rotation speed of 2rpm / min, crystal growth rate of 0.3mm / min, and the temperature in the single crystal furnace is controlled at 1600℃. The initial tensile strength of the crucible and the tensile strength after different use times are tested. The specific test results are shown in Table 4.

[0086] Table 4 Tensile strength of crucible after different time (unit: MPa)

[0087]

[0088]

[0089] It can be seen from Table 4 that in the process of preparing the coating, the conditions of chemical vapor deposition are: heating temperature is 1100°C, pressure is 2000Pa, composite gas is carbon source precursor and nitrogen, and the residence time of composite gas is 8s. The crucible obtained. As time goes by, the tensile strength of the crucible gradually decreases, and the tensile strength after 12 months is 37.8MPa, which is greater than 50% of the initial tensile strength of the crucible. Therefore, the service life of the crucible prepared in this application is more than 12 months.

[0090] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present application, but the present application is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present application, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a coating, characterized in that: The following steps are included: A coating is formed on the substrate by chemical vapor deposition, wherein the conditions of the chemical vapor deposition are: a heating temperature of 1095-1105°C, a pressure of 1500-2500Pa, a composite gas of a carbon source precursor and nitrogen, a residence time of the composite gas of 7s-12s, and a volume ratio of the carbon source precursor to the nitrogen of 1:(1-3).

2. The method for preparing the coating according to claim 1, characterized in that: The heating temperature is 1100-1105°C; The pressure is 1500-2000Pa; The residence time of the composite gas is 7s-10s.

3. The method for preparing the coating according to claim 1, characterized in that: The volume ratio of the carbon source precursor to the nitrogen gas is 1:(1-2).

4. The method for preparing the coating according to claim 1, characterized in that: The carbon source precursor is selected from alkanes, alkenes and alkynes having 1 to 4 carbon atoms.

5. The method for preparing the coating according to any one of claims 1 to 4, characterized in that: The matrix is ​​a carbon / carbon composite material.

6. A coating, characterized in that The coating is prepared by the method for preparing the coating according to any one of claims 1 to 5.

7. The coating according to claim 6, characterized in that: The coating has a loss amount ΔW%≤3.81% at 2000° C. for 100 hours, and a mass ablation rate Rm≤5.0 mg / s at 3000° C. for 20 seconds.

8. A product, characterized in that It comprises a substrate and the coating according to claim 6 or 7.

9. The product according to claim 8, characterized in that The product is a photovoltaic thermal field component or a heat shield component.

10. Use of the coating according to claim 6 or 7 in photovoltaic thermal field components and heat shielding components.

Citation Information

Patent Citations

  • Novel ultrahigh-temperature ceramic integrally-modified anti-ablation carbon / carbon composite material and preparation method thereof

    CN107021773A

  • Fine control method for alternately deposited multilayer pyrolytic carbon interface phase

    CN114988884A